PENGARUH KESADARAN WAJIB PAJAK, KUALITAS PELAYANAN FISKUS, TARIF PAJAK DAN KONDISI KEUANGAN TERHADAP KEPATUHAN WAJIB PAJAK KENDARAAN BERMOTOR (Studi Kasus Pada Wajib Pajak Orang Pribadi Yang Terdaftar di Samsat Ujung Batu) - Lestari, Wita; Yusralaini, Yusralaini; Safitri, Devi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2025)
This study aims to see (1) the effect of taxpayer awareness on taxpayer compliance (2) theeffect of the quality of tax services on taxpayer compliance (3) the effect of tax rates ontaxpayer compliance (4) the effect of financial conditions on taxpayer compliance. Thisstudy is a type of quantitative research. The source of research data is primary data withdata collection techniques using questionnaires. The population in this study were allindividual taxpayers registered at the Ujung Batu Samsat in 2019-2025. The samplingmethod in this study used incidental sampling techniques and used the Slovin formula todetermine the number of respondents. The sample used in this study was 100 taxpayers. Theresearch data was processed using PLS SEM with the smartPLS 4 application. The resultsof the study showed that taxpayer awareness, tax rates and financial conditions had apositive and significant effect on motor vehicle taxpayer compliance, while the quality of taxservices did not have a positive effect on motor vehicle taxpayer compliance.Keyword: taxpayer awareness, quality of tax services, tax rates, financial conditions,taxpayer compliance